APLIKASI ADMINISTRASI PEMBAGIAN DANA SEHAT PADA DESA SUNGAI SAHUT KEC. TABIR SELATAN KAB. MERANGIN - Sum Indra (JURNAL AKADEMIKA)
Dana sehat is an attempt to maintain the health of, by and for the people who organized based on the principle of joint ventures and familiarity with the pre-financing efforts and aims to improve public health. Dana sehat replied on Desa Sungai sahut has an important role in helping people to get funding through the distribution of fees pre-membership efforts. Dana Sehat as one of the Desa Sungai sahut Program Alert is one institution that can be used by communities as a source of financing at the time of illness and unnecessary delay because they do not have the money. Dana Sehat as one of the Desa Siaga Program which is one of the institutions that can be used by people as a source of financing at the time of illness and unnecessary delay because they do not have the money. Number of people who need assistance Dana Sehat, so the role of computers here is very important to help the processing of data at the Desa Sungai Sahut Office replied. Therefore we need an information system that can help the processing of data at the Desa Sungai Sahut Office said especially in the Administrative and so can control the data that existed at the Desa Sungai Sahut Office said the author of Programming using Microsoft Visual Basic 6.0, Using Microsoft Access as the Database and Crystal Report to print the report. Information systems are used to support the processing of data at the Desa Sungai Sahut office replied. With the use of the Microsoft Visual Basic 6.0 programming is expected to create and develop a computer program that can expedite and can efficiently use energy, time and simplify the data management activities at the Desa Sungai Sahut Office replied.